“Tudo que nóis tem é nóis”: a construção da identidade social discursiva em textos de Emicida - Nunziata, Thais Alencar Baptista (2024)
This study investigates the construction of social and discursive identities of the Brazilian black community in the discourse of rapper Emicida, focusing on the 5 albums "AmarElo" and "Principia". Based on the theoretical and methodological frameworks of French Discourse Analysis, as proposed by Maingueneau (1987, 1997, 2008, 2015) and Charaudeau (2009), the research also integrates contemporary debates on blackness, race, and identity from the perspectives of philosophy, anthropology, and sociology, highlighting the multidisciplinary nature of discourse analysis. The analysis reveals how Emicida employs interdiscursivity to connect religious, historical, cultural, and social discourses, creating a scenography that reflects the struggle and hope of the black community. Emicida's discursive ethos is authentic and representative, utilizing accessible and culturally relevant language that strengthens community bonds and promotes adherence. Through these resources, the rapper challenges dominant representations and offers an alternative narrative that values black culture and the fight for social justice. The results demonstrate that his discourse functions as a space of resistance, reinforcing the identity and self-esteem of the black community